Pitch perfect [videorecording (DVD)] - Moore, Jason, 1970-; Snow, Brittany, 1986-; Kendrick, Anna; Wilson, Rebel; Camp, Anna, 1982-; Rapkin, Mickey (Universal Home Entertainment, 2012)
Arriving at her new college, Beca finds herself not right for any clique but somehow is muscled into one that she never would have picked on her own: alongside mean girls, sweet girls and weird girls whose only thing in common is how good they sound when they sing together. When Beca leads this a cappella singing group out of their traditional arrangements and perfect harmonies into all-new mash-ups, they fight to climb their way to the top of college music competitions.